2007
DOI: 10.1007/s00464-007-9500-9
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year follow-up of laparoscopic Heller myotomy for achalasia shows durability

Abstract: Most patients who underwent LHM with partial fundoplication reported satisfaction 10 years after the operation. A small number of patients required additional intervention. Dysphagia scores at 10 years were not different from those collected at short-term follow-up. Our data suggest that the efficacy of LHM is sustained at 10-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…A number of studies have demonstrated that minimally invasive techniques also have excellent long-term relief of achalasia and the symptoms associated with dysphasia [12][13][14][15]. We feel that the benefits of minimally invasive surgery, in a large administrative database such as this, clearly demonstrate that, in patients who are candidates for minimally invasive myotomy, outcomes will be significantly improved over standard open operation.…”
Section: Discussionmentioning
confidence: 87%
“…A number of studies have demonstrated that minimally invasive techniques also have excellent long-term relief of achalasia and the symptoms associated with dysphasia [12][13][14][15]. We feel that the benefits of minimally invasive surgery, in a large administrative database such as this, clearly demonstrate that, in patients who are candidates for minimally invasive myotomy, outcomes will be significantly improved over standard open operation.…”
Section: Discussionmentioning
confidence: 87%
“…Laparoscopic Heller esophagomyotomy has produced favorable results for dysphagia in most cases of achalasia, with a response rate of approximately 90% [5,6]. As for the effect on chest pain, some studies have found the procedure to be effective [4,[9][10][11][12], whereas others have reported contradicting results [3,13,14]. Eckardt and Eckardt [15] stated in their review that this still is a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of symptoms was evaluated by a modified symptom score [17] , which consisted of the sum of the scores for dysphagia, regurgitation and chest pain. Recurrent achalasia is defined as recurrence of severe symptoms of dysphagia, regurgitation or chest pain (symptom scores of 2 or 3), and the need for intervention again, or repeat HM [18][19][20][21][22] . Data regarding the first author, year of publication, first-line treatment, operation duration, median hospital stay, and symptoms remission rate, were extracted.…”
Section: Study Selection and Data Analysismentioning
confidence: 99%